GLObfus: An Innovative Method of Data Obfuscation to Protect Numerical Data in Public Cloud Storage - D. I. George Amalarethinam; Lalu P. George (Mathematics and Computer Science: Contemporary Developments Vol. 4, 2024)
Cloud computing has modified computing services with global convenience and accessibility. Many users undervalue the security risks associated with cloud data despite its integration into daily life. Data breaches can occur without user awareness, emphasizing the need for robust security measures. Cloud servers globally manage vast data volumes in real-time, posing ongoing security challenges. Protecting data from unauthorized access is of great necessity in cloud computing research. Numerical data security in the cloud can be enhanced by using GLObfus, an innovative method of data obfuscation. GLObfus transforms data into an unintelligible format using advanced mathematical calculations. Through this obfuscation method and different types of keys, GLObfus ensures that sensitive numerical data, such as student’s marks and financial details, are rendered in an unintelligible format. This approach mitigates the risks of data exposure and unauthorized access by obscuring data before it is stored in the cloud. Operational efficiency and data security are significantly enhanced by GLObfus, which operates as a cloud utility within a Platform-as-a-service (PaaS) framework. Evaluations have demonstrated that GLObfus surpasses existing obfuscation techniques in terms of reusing time and increasing security measures. This makes it particularly well-suited for organizations that give priority to robust data protection in cloud environments, thereby establishing new security standards in the digital era.